Managing Large Enrollment Courses in Hybrid Instruction Mode - Pooja Khanna (Laureate Education Inc, 2016)
While Indian education system is still debating on values of Gurukal system to imperial western education; the world moves on to the hybrid teaching learning system. Though the western world started hybrid teaching in early 1990's, it took us good 30 years to follow the Westroes. Even when we have initiated the process in few institutions there is much to understand and do before we actually get to see the success of Hybrid online teaching and learning. This paper set to study the hitches and glitches in Hybrid Instruction system of teaching and learning for large enrollment courses. This new instructional methodology ask for redesigning the entire traditional teaching and learning practices where motivation of the felicitator is of prime concern that whether they are motivated enough to come out of their comfort zones.